2020
DOI: 10.1080/09645292.2020.1761945
|View full text |Cite
|
Sign up to set email alerts
|

Minority report: the impact of predicted grades on university admissions of disadvantaged groups

Abstract: We study the UK's university application system, in which students apply based on predicted examination grades, rather than actual results. Using three years of UK university applications data we find that only 16% of applicants' predicted grades are accurate, with 75% of applicants having over-predicted grades. However, high-attaining, disadvantaged students are significantly more likely to receive pessimistic grade predictions. We show that under-predicted candidates are more likely to enrol in courses for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 13 publications
0
28
1
1
Order By: Relevance
“…Previous research has found that A Level predictions for students in the UK are inaccurate (Everett and Papageourgiou, 2011;UCAS, 2016) with only 16% of grades predicted by teachers being reflected in actual grades achieved (Murphy and Wyness, 2020). Inaccurate predictions of A Level grades are particularly problematic for students intending to progress to university.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has found that A Level predictions for students in the UK are inaccurate (Everett and Papageourgiou, 2011;UCAS, 2016) with only 16% of grades predicted by teachers being reflected in actual grades achieved (Murphy and Wyness, 2020). Inaccurate predictions of A Level grades are particularly problematic for students intending to progress to university.…”
Section: Introductionmentioning
confidence: 98%
“…The Sutton Trust's analysis of students from less affluent families noted the greater impact inaccurate predictions of grades had on their university choices often leading, 'many disadvantaged students to make sub-optimal decisions when choosing their universities' (Wyness 2017: 3). Grades for students from ethnic minorities are often over-predicted by teachers; the inaccuracy of such predictions similarly results in poorer outcomes when students do not achieve the grades they require for their first choice university (Murphy and Wyness, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…У зависности од трајања стања које подразумева затворене образовне институције, широм света ће највероватније бити примењене сличне мере. Једна потенцијална алтернатива за отказано оцењивање јесу предвиђене оцене, али Марфи и Вајинс (Murphy & Wyness, 2020) показују да оне често нису веродостојне, и да су предвиђене оцене за ученике из незавидних економских средина ниже него код ученика вишег економског статуса. Друго решење је оцењивање на основу процене наставника, уместо тестова и испита.…”
Section: оцењивањеunclassified
“…Even France, from which we inherited this certificate with all its organizational complications and social and psychological burdens, decided to cancel the final exam that leads to its achievement, and only to calculate the marks of continuous monitoring. On the other side of Latin Europe, England followed another path, though it also canceled the certification examinations, but decided to adopt a complex rule to determine the level of the student based on all the assignments and works he accomplished, in addition to his institution's estimates about the marks that he could have obtained If the exams took place normally (Murphy & Wyness , 2020). In order for the process to be more equitable for the English pupils, it will be available for those who saw that the estimated marks do not reflect its true level, to pass the certification examination when schools open.…”
Section: Urgent Measures To Get Out Of the Crisismentioning
confidence: 99%